The Democratic Republic of Congo’s Infrastructure : A Continental Perspective - Foster, Vivien; Benitez, Daniel Alberto (2012)
The Democratic Republic of Congo (DRC) faces possibly the most daunting infrastructure challenge on the African continent. Conflict has seriously damaged most infrastructure networks. Vast geography, low population density, extensive forestlands, and criss-crossing rivers complicate the development of new networks. Progress has been made since the return of peace in 2003. A privately funded GSM network now provides mobile telephone signals to two-thirds of the population. External funding has been secured to rebuild the country's road network, and domestic air traffic has grown. Modest investments could harness inland waterways for low-cost transport. Much more substantial investments in hydropower would enable the DRC to meet its own energy demands cheaply while exporting vast quantities of power. One of the country's most immediate infrastructure challenges is to reform the national power utility and increase power generation and delivery. Capacity must increase by 35 percent over the period 2006-15 to meet domestic demand. The dilapidated condition of both road and rail infrastructure presents another challenge. To meet the target defined in the report, investment in the country's infrastructure must increase from $700 million to $5.3 billion per year over the next decade, a staggering 75 percent of 2006 GDP. New infrastructure technologies, the elimination of inefficiencies, and cross-border finance (for hydropower development) could cut the annual funding gap in half. Recently, the country secured $4 billion in external finance commitments for infrastructure, enabling increases in budget allocations for public investment.